Multidisciplinary approach to the treatment of invasive fungal infections in adult patients. Prophylaxis, empirical, preemptive or targeted therapy, which is the best in the different hosts? - Rafael Zaragoza; Javier Pemán; Miguel Salavert; Ángel Viudes; Amparo Solé et al (Dove Medical Press, 2008)
Rafael Zaragoza1, Javier Pemán2, Miguel Salavert3, Ángel Viudes2, Amparo Solé4, Isidro Jarque5, Emilio Monte6, Eva Romá6, Emilia Cantón71Servicio de Medicina Intensiva, Hospital Universitario Dr Peset, Valencia, Spain; 2Servicio de Microbiología; 3Unidad de Enfermedades Infecciosas; 4Unidad de Trasplante Pulmonar; 5Servicio de Hematología; 6Servicio de Farmacia; 7Unidad de Microbiología Experimental, Centro de Investigación, Hospital Universitario La Fe Valencia, SpainAbstract: The high morbidity, mortality, and health care costs associated with invasive fungal infections, especially in the critical care setting and immunocompromised host, have made it an excellent target for prophylactic, empiric, and preemptive therapy interventions principally based on early identification of risk factors. Early diagnosis and treatment are associated with a better prognosis. In the last years there have been important developments in antifungal pharmacotherapy. An approach to the new diagnosis tools in the clinical mycology laboratory and an analysis of the use new antifungal agents and its application in different clinical situations has been made. Furthermore, an attempt of developing a state of the art in each clinical scenario (critically ill, hematological, and solid organ transplant patients) has been performed, trying to choose the best strategy for each clinical situation (prophylaxis, pre-emptive, empirical, or targeted therapy). The high mortality rates in these settings make mandatory the application of early de-escalation therapy in critically ill patients with fungal infection. In addition, the possibility of antifungal combination therapy might be considered in solid organ transplant and hematological patients.Keywords: invasive fungal infections, prophylaxis, empirical therapy, preemptive treatment, targeted therapy